Is short term intraoperative application of disinfectants harmful to breast implants in breast reconstruction? An experimental study and literature survey. (February 2019) - Schmitz, Marweh; Schubert, Dirk W.; Kaschta, Joachim; Daenicke, Jonas; Walter, Bastian L.; Horch, Raymund E.
Abstract: Objectives: Bacterial contamination of breast implants and biofilm formation has been discussed as a major reason for implant loss and capsular contraction. Intra- and perioperative treatment of breast implants with disinfectants to prevent bacterial contamination has been frequently reported. Given the increasing awareness of concerns about product liability the question of whether short-time irrigation of implants with antimicrobial substances during the operative procedure would potentially alter the integrity of the implant shell has attracted legal and medical interest. In this study we therefore investigated whether irrigating breast implants with antimicrobials commonly used in clinical practice with a clinically relevant application time would affect the physical integrity of the implant shell. Materials and methods: Samples, which were previously punched from the shell of explanted standard silicone gel filled breast implants in a defined way, were exposed to different disinfectant solutions for two minutes. Multiple defined specimens from 5 different explants from 4 different producers (including PIP) were tested. The testing included tensile strength and disruption tests. Results: In our prospective test series we could not find a significant influence of a single distinct disinfectant on silicone shell implant surfaces. Conclusion: Despite the potential legal implications that might be considered when a surgeon manipulates an implant with disinfectants intraoperatively, we find it worthwhile to state that from a material and surgical standpoint there is no evidence that short-time treatment of alloplastic materials would be detrimental to the physical properties of the implant shell.